2022
DOI: 10.1098/rsos.211345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced mobility on trabecular bone density in captive big cats

Abstract: Bone responds to elevated mechanical loading by increasing in mass and density. Therefore, wild animals should exhibit greater skeletal mass and density than captive conspecifics. This expectation is pertinent to testing bone functional adaptation theories and to comparative studies, which commonly use skeletal remains that combine zoo and wild-caught specimens. Conservationists are also interested in the effects of captivity on bone morphology as it may influence rewilding success. We compared trabecular bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 104 publications
(153 reference statements)
0
13
1
Order By: Relevance
“…Third, as noted previously, although using home range size as a proxy for mobility is practical, home range sizes vary widely depending on factors such as seasonality, resource availability, and geographic space available; therefore, some of the species have overlapping home ranges, thus making the distinctions unclear. Fourth, Chirchir et al (2022) and Zack et al (2022) showed the value of separating wild versus captive specimens when conducting morphological studies using museum collections; this study attempted to study only wild-caught samples however, due to still a small sample available we included both wild and specimens of "unknown" origin (Table 1) to increase the data's statistical robusticity and while small in sample size, some of those specimens could have been derived from zoos which would slightly skew our results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Third, as noted previously, although using home range size as a proxy for mobility is practical, home range sizes vary widely depending on factors such as seasonality, resource availability, and geographic space available; therefore, some of the species have overlapping home ranges, thus making the distinctions unclear. Fourth, Chirchir et al (2022) and Zack et al (2022) showed the value of separating wild versus captive specimens when conducting morphological studies using museum collections; this study attempted to study only wild-caught samples however, due to still a small sample available we included both wild and specimens of "unknown" origin (Table 1) to increase the data's statistical robusticity and while small in sample size, some of those specimens could have been derived from zoos which would slightly skew our results.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated trabecular bone morphology in four felid species: cheetahs ( Acinonyx jubatus, n = 20), jaguars ( Panthera onca, n = 9), leopards ( Panthera pardus, n = 15), and cougars ( Puma concolor, n = 18). We selected these species because of their diversity in locomotor behavior, varied home range sizes, and their fairly close phylogenetic relationship (Werdelin et al, 2010; also see Chirchir et al, 2022). The skeletal specimens were obtained from the National Museum of Natural History; the Smithsonian Institution in Washington, DC; and the American Museum of Natural History, New York (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations